Fitness and evolution of insecticide resistance associated with gut symbionts in metaflumizone-resistant Plutella xylostella. (October 2019) - Li, Dongyang; Zhang, Yunhua; Li, Wenhao; Tang, Tao; Wan, Hu; You, Hong; Li, Jianhong
Abstract: Insects harbor symbionts that have been observed to change the fitness of the host. In the present study, we investigated the variations in symbiont composition of the metaflumizone-resistant strain of Plutella xylostella (MR), which has showed 1372.83-fold higher resistance to metaflumizone than the susceptible strain of P. xylostella (SS), with a relative fitness cost of 0.78 under the same genetic background base on 16SrDNA sequencing. The results showed that the MR and SS differ greatly in their respective symbiont compositions, with the MR showing a large proportion of Proteobacteria and the SS having a high abundance of Firmicutes bacteria. These two main microbial phyla compose approximately 80% of the whole microbial community. Furthermore, a higher diversity of symbiont species in the MR was observed, which manifested through the alpha diversity indexes of Chao1 and ACE (Abundance-based Coverage Estimators) as well as the PD (phylogenetic diversity) whole tree. Additionally, the metagenome functional content was predicted by Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt), demonstrating a significant difference between the MR and SS in the relative abundance of the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Metabolic enhancement in a variety of energy and nutrient pathways was demonstrated in the gut symbionts of the MR; however, xenobiotic metabolism was decreased in the MR, which suggested that gut symbionts may contribute to the decrease in the MR fitness but do not directly participate in the metabolism of metaflumizone. These results lay a foundation for future study of the mechanism of resistance to metaflumizone mediated via gut symbionts in P. xylostella. Graphical abstract: Image 1 Highlights: The gut symbiont compositions between the SS and MR were investigated. The decrease fitness may be involved in the metabolic pathways of the gut symbionts. Different symbionts compositions may be the key of host response to metaflumizone.